Hepatitis C virus targets the T cell secretory machinery as a mechanism of immune evasion. - Long, Aideen; Petrovic, Danijela; Stamataki, Zania; Dempsey, Eugene; Golden-Mason, Lucy; Freeley, Michael; Doherty, Derek; Prichard, David; Keogh, Catherine; Conroy, Jennifer; Mitchell, Siobhan; Volkov, Yuri; et al. (My University, 2011)
T cell activation and the resultant production of interleukin (IL-2) is a central response of the adaptive immune system to pathogens, such as hepatitis C virus (HCV). HCV uses sev- eral mechanisms to evade both the innate and adaptive arms of the immune response. Here we demonstrate that liver biopsy specimens from individuals infected with HCV had significantly lower levels of IL-2 compared with those with other inflammatory liver dis- eases. Cell culture–grown HCV particles inhibited the production of IL-2 by normal peripheral blood mononuclear cells, as did serum from HCV-infected patients. This pro- cess was mediated by the interaction of HCV envelope protein E2 with tetraspanin CD81 coreceptor. HCV E2 attenuated IL-2 production at the level of secretion and not transcrip- tion by targeting the translocation of protein kinase C beta (PKC b ), which is essential for IL-2 secretion, to lipid raft microdomains. The lipid raft disruptor methyl- b -cyclodextrin reversed HCV E2-mediated inhibition of IL-2 secretion, but not in the presence of a PKC b -selective inhibitor. HCV E2 further inhibited the secretion of other cytokines, including interferon- c . Conclusion: These data suggest that HCV E2–mediated disruption of the association of PKC b with the cellular secretory machinery represents a novel mecha- nism for HCV to evade the human immune response and to establish persistent infection.
PUBLISHED
Keywords: T cell activation; Immunity; Hepatitis C; Immunology, Inflammation & Infection